2017
DOI: 10.1088/1757-899x/245/4/042058
|View full text |Cite
|
Sign up to set email alerts
|

City and Urbanity in the Social Discourse

Abstract: Abstract. The aim of our article is an attempt to present the concept of urbanity that has been shaped throughout centuries along with the development of European civilisation and now entered a new phase of social production of space based on cultural dimensions. The future of the majority of World's population is connected currently with the urban life with the assumption that qualitative characteristics of life in the 21st century define the quality of civilisation itself. Contrary to many scientists' predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Cities become tools of impersonal life and the term "urban" more often refers to group or tribal experiences based on the principles of temporary community, where people come together to solve certain problems and participate in certain events only to disperse when finished. (Dymnicka and Badach, 2017). So if it is observed that urban culture, bottom-up initiatives and pop-up projects will become increasingly significant, in providing answers to changing needs and aspirations of urban users.…”
Section: Urbanity City Lifementioning
confidence: 99%
“…Cities become tools of impersonal life and the term "urban" more often refers to group or tribal experiences based on the principles of temporary community, where people come together to solve certain problems and participate in certain events only to disperse when finished. (Dymnicka and Badach, 2017). So if it is observed that urban culture, bottom-up initiatives and pop-up projects will become increasingly significant, in providing answers to changing needs and aspirations of urban users.…”
Section: Urbanity City Lifementioning
confidence: 99%